Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 581 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Anoura geoffroyi Gray, 1838", "Geometry POLYGON((-85.04 -0.33,-85.04 11.82,-65.82 11.82,-65.82 -0.33,-85.04 -0.33))", "HasGeospatialIssue is false" ] } The dataset includes 581 records from 20 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0014464-151016162008034/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences